PENGEMBANGAN MODEL PRAKTIKUM RANGKAIAN LISTRIK BERBASIS MASALAH UNTUK MENINGKATKAN KETERAMPILAN SCIENTIFIC INQUIRY MAHASISWA - Simatupang, Sehat; Simanjutak, Mariati Purnama (Jurnal Pendidikan Progresif, 2016)
The Application of Problem-Based Electric Circuit Practicum Model of Students’ Scientific Inquiry Skills. The study was conducted by the method of research and development. This research was conducted in the laboratory of physics education of FPMIPA, University of Medan. The result product is a problem-based learning media, practical tools and Problem-Based Electric Circuit Labwork Learning Model which can improve the results of scientific inquiry. The results of this research is that the Problem-Based Electric Circuits Labwork Learning Model development is still in the limited testing phase. Based on the limited test results, by applying the Problem-Based Electric Circuit Labwork Learning Model, there is an increasing in the scientific inquiry in the medium category. Keywords: problem-based learning model, scientific inquiry skill, electric circuit labwork, cognition DOI: http://dx.doi.org/10.23960/jpp.v6.i1.201601